Sustainable Service Qualty Model (SSQ) and Customer Loyalty: Muslim-Friendly Hospitality Services (MFHS) in Malaysia - Muhamad Azrin Nazri; Azreen Jihan Che Mohd Hashim; Sumaiyah Abd Aziz; Nor Asiah Omar (Borneo Tourism Research Centre (BTRC), 2025)
Non-Indexed Publication